Molecular and biological properties of the Newcastle disease virus strain of virulent genotype VII, first isolated in 2008 from a wild duck in the Republic of Adygea, Russia - A. V. Glushchenko; K. S. Yurchenko; L. S. Adamenko; Yu. I. Karkavin (Юг России: экология, развитие)
Aim. To study some biological properties of the obtained strain of Newcastle disease virus NDV/Adygea/duck/12/2008, including the degree of virulence, and to conduct a phylogenetic study.Biological material from wild migratory birds was collected in 2008 during the hunting season. Isolation and cultivation of the isolated strains were carried out in the system of developing chicken embryos (RCE). Primary identification confirming the presence of a hemagglutinating agent in the allantoic fluid was carried out in the hemagglutination reaction (HR). Pathogenicity was assessed by MDT and ICPI methods. Sequencing, phylogenetic analysis, the genotype of the studied strain was determined.The results of studying the main biological properties of the Newcastle disease virus strain NDV/Adygea/duck/12/2008, isolated from wild migratory birds in the Southern Federal District, are presented. According to the phylogenetic study, the NDV/Adygea/duck/12/2008 strain belongs to genotype VII and genetic class 2. The MDT and ICPI virulence tests, as well as the molecular genetic study, classified the described strain as highly pathogenic.